Correspondence 1904-1938 - Freud, Sigmund 1856-1939; Freud, Anna 1895-1982 (Polity Press, 2014)
The correspondence ranges over personal and family matters - social events, family holidays, births and deaths, health issues, war experiences, etc. - as well as professional matters, including the progress of Sigmund Freud's and Anna Freud's scientific works, their views on students and colleagues, and the international dissemination and publication of psychoanalytical writings. The letters provide valuable insight into the work and family life of the founder of psychoanalysis, Sigmund Freud, including the changes in his perception of women that were triggered by his relation with his daughter. They also shed fresh light on the development of Anna's life and career - the early years in England, the period of her analysis with her own father and the last phase of her father's illness and death, when Anna became the torch-bearer and protector of her father's works, and eventually became the leading figure in the International Psychoanalytic Association. Richly annotated with editorial comments, this unique volume of correspondence between Sigmund and Anna Freud is an invaluable source of historical documentation about the formation and development of psychoanalysis and the early decades of the psychoanalytic movement. -- Provided by publisher.